Prediction of the intensity and diversity of day-to-day activities among people with schizophrenia using parameters obtained during acute hospitalization. Issue 13 (19th June 2017) - Lipskaya-Velikovsky, Lena; Jarus, Tal; Kotler, Moshe
Abstract: Purpose: Participation in day-to-day activities of people with schizophrenia is restricted, causing concern to them, their families, service providers and the communities at large. Participation is a significant component of health and recovery; however, factors predicting participation are still not well established. This study examines whether the parameters obtained during acute hospitalization can predict the intensity and diversity of participation in day-to-day activities six months after discharge. Method: In-patients with chronic schizophrenia ( N  = 104) were enrolled into the study and assessed for cognitive functioning, functional capacity in instrumental activities of daily living (IADL), and symptoms. Six months after discharge, the intensity and diversity of participation in day-to-day activities were evaluated ( N  = 70). Results: Multiple correlations were found between parameters obtained during hospitalization and participation diversity, but not participation intensity. The model that is better suited to the prediction of participation diversity contains cognitive ability of construction, negative symptoms and number of previous hospitalizations. The total explained variance is 37.8% (F3, 66  =  14.99, p  < 0.001). Conclusions: This study provides evidence for ecological validity of the in-patient evaluation process for the prediction of participation diversity in day-to-day activities six months after discharge. Participation diversity is best predicted through a set of factors reflecting personal and environmental indicators. Implications for rehabilitation: Results of in-patient evaluations can predict the diversity of participation in day-to-day activities six months after discharge. Higher prediction of participation diversity is obtained using a holistic evaluation model that includes assessments for cognitive abilities, negative symptoms severity and number of hospitalizations.